Role of adiponectin and nsafatin_1 hormones in polycystic ovary syndrome: systematic review - Narjes Hasanheyvadi; Fatemeh Razavinia; Fatemeh Yahyavi Koochaksaraei; Sedighe Rezaei Chamani (Mashhad University of Medical Sciences, 2020)
Introduction: Adiponectin and nesfatin are the hormones which secret from adipose tissue in response to extracellular stimuli. Lipid metabolism and insulin sensitivity have role in regulating energy balance. This review study was performed with aim to investigate the effect of adiponectin and nesfatin-1 in polycystic ovary syndrome (PCOS).  Methods: In this review article, to find the articles, search was performed in databases of pubmed, google scholar, Scopus, SID with the keywords of Adiponectin, Nesfatin, and polycystic ovary syndrome from 2003 to 2017. This study was written based on PRISMA checklist. The quality of the extracted articles was evaluated based on the STORBE, CONSORT and CASP checklist of contents, and ultimately 21 articles were assessed.  Results: In most studies, adiponectin levels have been shown to decrease in patients with PCOS. Also, the studies have shown contradictory results about nesfatin levels and PCOS. Conclusion: Studies have shown that adiponectin and nesfatin may play a role in PCOS and likely control and regulate this hormone in the body and can help to treat people with PCOS or prevent it and reduce the economic burden on the family and society.